Tale Haji: The Uncovering Tradition In Kerinci District - Putri, Atika; Andrian, Riko (Contemporary Society and Politics Journal, 2022)
Talking about the Kerinci district this article will discuss one of the traditions in the Kerinci district, namely Tale Haji. It is a song sung by pilgrims who want to go to Haji using their local languages. In its implementation, all family members and the community gather in one house to release the pilgrims by singing or listening to them. The article uses qualitative methods to produce data and information about the history of Tale Haji in the tradition of the Pungut Hilir community of the Kerinci district. In this article, the researcher looks at various aspects, namely the history of the Tale Haji, the implementation of the Tale Haji in community life, and the meaning of the Tale Haji. This article research also aims to give more information and better understand the traditions in Kerinci Regency, one of which is the Tale Haji tradition. This research can also be a guide and reference for further research about the Tale Haji tradition.